Hadith #6792 - Sahih al-Bukhari - Junadah bin Abi Umayya (Sahih al-Bukhari)
We entered upon ‘Ubada bin As-Samit while he was sick. We said, “May Allah make you healthy. Will you tell us a Hadith you heard from the Prophet (ﷺ) and by which Allah may make you benefit?” He said, “The Prophet (ﷺ) called us and we gave him the Pledge of allegiance for Islam, and among the conditions on which he took the Pledge from us, was that we were to listen and obey (the orders) both at the time when we were active and at the time when we were tired, and at our difficult tim
Grade: Sahih